Severnsia strombeulima n. gen. & sp. from Hawaii (Mollusca, Gastropoda: Caenogastropoda: Eulimidae) - Geiger, Daniel L. (Zootaxa, 2016)
The malacofauna of Hawaii is rather well-known, owing to Kay (1979) and Severns (2011). Both works stand out because they include a large number of the generally under-represented micromollusks (<5 mm). Here a striking new genus and species of a microsnail is reported from that region.